Factors associated with shea butter processing in Kwara State, Nigeria (2014)
The need to improve the production of shear butter as a means of sustainable livelihood and monetary income for rural dwellers in the nation necessitated this study. The factors associated with shea butter processing were assessed in this study. Interview schedule was employed to elicit information from the respondents. Structured interview schedule was administered to 160 randomly sampled shear butter processors in Kwara State. Data obtained were subjected to descriptive and inferential statistics. Results of the study revealed that majority of the processors were females, elderly, married with little or no formal education. They had large household size with shea butter processing being their primary occupation. Processing techniques adopted by respondents were rudimentary, laborious and time consuming. Processors identified rainfall as a very important climatic factor, knowledge of improved technologies as a very important factor, access to credit facilities as a germane economic factor, availability of water as a very important physical factor associated with Shea butter processing. Insufficient water, bad road networks and lack of credit were very severe constraint among the respondents. There is thus the need by the state government to provide more basic infrastructural facilities like water, electricity, rural feeder roads to enhance the capacity of Shea butter processors. Association of respondents with cooperative societies should be encouraged through extension education to boost their productivity in meeting up with the demands for domestic consumption, export and family bills.